Potential Hazards in the Loading and Unloading Process: Risk Analysis with Job Safety Analysis and Hazard Operability Study Methods - Ramisdar, Irma Octaviani; Ibrahim, Hasbi; Mallapiang, Fatmawaty; Lagu, Abdul Majid H.R. (Diversity: Disease Preventive of Research Integrity, 2020)
Loading companies have a high accident risk because the services that they provide involve a lot cargo moving in out of cargo ships. Job Safety Analysis (JSA) and Hazard and Operability Study (HAZOPs) are common risk management procedures that a company should follow to ensure the safety of the workers by measuring the risks and preparing strategies to control the hazards. This research aims to identify, assess and manage the occupational health and safety of the workers during loading processes in the container terminal of PT Pelindo IV (persero) in Makassar in 2019. It investigates the issue by employing descriptive quantitative method and observational approach. Observational approach allows this research to describe the stages of loading process through observations that utilize work sheet Job Safety Analysis (JSA), Hazard and Operability Study (HAZOPs) and AS/NZS 4360:2004. The research samples consist of 157 respondents who are selected using proportionate stratified random sampling technique. The research findings identify some hazards of loading process including physical, mechanical and ergonomic hazards with mechanical hazard having the highest level of hazard by 74.5% particularly in Haulage/Trucking area. The risk assessment indicates that undesirablerisks on the first, third, fourth and fifth work stages are categorized into acceptable with control on the second work stage.